Challenges faced by auditors due to lack of clients cooperation - Saidi, Nursafa Dhamirah; Ishak, Rosbi (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The difficulties auditors have as a result of uncooperative clients are covered in this article. These difficulties include insufficient documentation, delays, and the absence of important staff members. These issues lengthen audit timelines, raise expenses, and lower audit quality. Relationship tensions between auditors and clients can also result from non-cooperation, which can be caused by things like power struggles, inadequate communication, and client anxieties about being scrutinized. Qualified opinions, harm to one's reputation, and a decline in investor trust are among the repercussions. In order to overcome these obstacles, tactics including client education, transparent communication, and frequent consultations are advised in order to enhance teamwork, foster confidence, and guarantee effective, trustworthy audits while preserving the accuracy of financial reporting.